Impact of shock index (SI), modified SI, and age-derivative indices on acute heart failure prognosis; A systematic review and meta-analysis. - Mehrbod Vakhshoori; Niloofar Bondariyan; Sadeq Sabouhi; Mehrnaz Shakarami; Sayed Ali Emami; Sepehr Nemati; Golchehreh Tavakol; Behzad Yavari; Davood Shafie (PLoS ONE)
Background Heart failure (HF) is still associated with quite considerable mortality rates and usage of simple tools for prognosis is pivotal. We aimed to evaluate the effect of shock index (SI) and its derivatives (age SI (ASI), modified SI (MSI), and age MSI (AMSI)) on acute HF (AHF) clinical outcomes. Methods PubMed/Medline, Scopus and Web of science databases were screened with no time and language limitations till February 2024. We recruited relevant records assessed SI, ASI, MSI or AMSI with AHF clinical outcomes. Results Eight records were selected (age: 69.44±15.05 years). Mean SI in those records reported mortality (either in-hospital or long-term death) was 0.67 (95% confidence interval (CI):0.63-0.72)). In-hospital and follow-up mortality rates in seven(n = 12955) and three(n = 5253) enrolled records were 6.18% and 10.14% with mean SI of 0.68(95%CI:0.63-0.73) and 0.72(95%CI:0.62-0.81), respectively. Deceased versus survived patients had higher SI difference (0.30, 95%CI:0.06-0.53, P = 0.012). Increased SI was associated with higher chances of in-hospital death (odds ratio (OR): 1.93, 95%CI:1.30-2.85, P = 0.001).The optimal SI cut-off point was found to be 0.79 (sensitivity: 57.6%, specificity: 62.1%). In-hospital mortality based on ASI was 6.12% (mean ASI: 47.49, 95%CI: 44.73-50.25) and significant difference was found between death and alive subgroups (0.48, 95%CI:0.39-0.57, P<0.001). Also, ASI was found to be independent in-hospital mortality predictor (OR: 2.54, 95%CI:2.04-3.16, P<0.001)). The optimal ASI cut-off point was found to be 49.6 (sensitivity: 66.3%, specificity: 58.6%). In terms of MSI (mean: 0.93, 95%CI:0.88-0.98)), significant difference was found specified by death/survival status (0.34, 95%CI:0.05-0.63, P = 0.021). AMSI data synthesis was not possible due to presence of a single record. Conclusions SI, ASI, and MSI are practical available tools for AHF prognosis assessment in clinical settings to prioritize high risk patients.